Coastal Settlement Sanitation Facilities In an Effort to Alleviate Environmental Factors to Overcome Stunting In Paluh Sibaji Village - Indirawati, Sri Malem; Salmah, Umi; Mahyuni, Eka Lestari; Saragih, Izzah Djenillah; Lestari, Annisa Rizka; Sembiring, Meryntha Andrey Tiara; Hutagaol, Stepani Angeline (Universitas Negeri Medan, 2024)
Sanitation of the residential environment, people in Paluh Sibaji village experience limited basic sanitation in the form of limited clean water facilities and minimal toilet facilities far from health requirements. Based on this, the community of Paluh Sibaji village is experiencing health problems related to environment-based diseases and stunting was found to be 60 cases of stunting in Pantai Labu sub-district in 2023. The methods used in handling the problem are atmosphere building, action diagnosis, socialisation, education and intervention to revitalise latrines and clean water sources in hamlet IV of Paluh Sibaji Village. The latrines and clean water sources that have been renovated have met the requirements of healthy latrines and clean water. Evaluation continues to be conducted regularly to improve and maintain the sustainability of the programme.